Peran Pendidikan Agama Kristen (PAK) dalam Membangun Karakter Mahasiswa untuk Menghindari Perilaku Kumpul Kebo - Endi Tanaem; Hedrik A. E. Lao (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The purpose of this article study is to analyze the Role of Christian Religious Education (PAK) in Building Student Character to Avoid Cohabitation Behavior. Using a qualitative research approach, data were collected through unstructured interviews, non-participant observation, and literature studies from relevant journals and books. The results of the study indicate that although PAK teaches moral values ​​such as love, honesty, and responsibility, many students have difficulty in implementing them due to the influence of a loose boarding environment and peer pressure. Students are often trapped in unhealthy relationships and ignore Christian principles because they feel pressured to follow the behavior of others. In addition, social skills such as interaction and empathy that should be developed through PAK are also hampered by social norms around them. This study emphasizes the need for social support and a contextual educational approach so that students can more effectively apply moral values ​​in social interactions. To reduce cohabitation behavior, educational institutions need to create an environment that supports the implementation of PAK values ​​consistently.